Treatment Variability and Complications Associated With Pediatric Lateral Ankle Injuries: A POSNA Quality, Safety, and Value Initiative Survey. Issue 6 (1st June 2022) - Beck, Jennifer J.; Carpenter, Connor M.; West, Nicole; Sabatino, Meagan J.; Ellis, Henry B.
Background: Isolated pediatric lateral ankle injuries, including ankle sprain (AS) and nondisplaced Salter-Harris type 1 (SH-1) distal fibular fracture, are common orthopaedic sports-related injuries. Variability in treatment is suspected among pediatric orthopaedic surgeons. Complications from medical treatment or lack thereof have not been reported in this population. Purpose: The purpose of this study was to investigate treatment variability and associated complications after pediatric AS and SH-1 via a survey of members of the Pediatric Orthopaedic Society of North American (POSNA). Study Design: Cross-sectional study. Level of evidence, 5. Methods: A voluntary, anonymous survey was distributed to POSNA membership (approximately 1400 members) via email. Survey questions, specific to both grade 1 or 2 AS and nondisplaced or minimally displaced SH-1 injuries in skeletally immature patients, focused on initial evaluation, immobilization, return to sports, and complications. We analyzed variability both in treatment between AS and SH-1 injury and in respondent characteristics. For statistical analysis, chi-square or Fisher exact test was used for categorical variables, and analysis of variance was used for continuous variables. Results: The survey response rate was 16.4% (229/1400). Of the respondents, 27.7% used examination only to distinguish between AS and SH-1, whereas 18.7% performed serial radiography to aid with diagnosis. A controlled ankle motion boot or walking boot was the most common immobilization technique for both AS (46.3%) and SH-1 (55.6%); the second most common technique was bracing in AS (33.5%) and casting in SH-1 (34.7%). Approximately one-third of all respondents recommended either outpatient or home physical therapy for AS, whereas only 11.4% recommended physical therapy for SH-1 ( P < .01). Results showed that 81.2% of respondents reported no complications for SH-1 treatment and 87.8% reported no complications for AS treatment. Cast complications were reported by 9.6% for SH-1 and 5.2% for AS. Rare SH-1 complications included distal fibular growth arrest, infection, nonunion, late fracture displacement, and recurrent fracture. Conclusion: Significant variability was found in primary treatment of pediatric AS and SH-1 injuries. Rare complications from injury, treatment, and neglected treatment after SH-1 and AS were reported.